ALK Deletion Exons 2 to 19: Case Report of a Rare ALK Inhibitor–Responsive Lung Cancer Driver Oncogene - Zachary R. Schoepflin, MD; Emmeline Academia, PharmD; Soravis A. Osataphan, MD; Deepa Rangachari, MD; Sheida Sharifi, MD, PhD; Paul A. VanderLaan, MD, PhD; Daniel B. Costa, MD, PhD (JTO Clinical and Research Reports, 2023)
ALK internal deletions of nonkinase domain exons occur in 0.01% of lung cancers with ALK genomic aberrations. We report a lung adenocarcinoma with a previously undescribed somatic ALK deletion of exons 2 to 19 with dramatic and sustained (>23 mo) response to alectinib. Our and other reported cases with ALK nonkinase domain deletions (between introns and exons 1–19) can display positive results in nonsequencing-based lung cancer diagnostic tests (such as immunohistochemistry) used to screen for more common ALK rearrangements. This case report emphasizes that “ALK-driven” lung cancers should be expanded to encompass those harboring not only ALK rearrangements with other genes but also ALK nonkinase domain deletions.